DÄ«nÄmikiyyah Jamâ€™iyyah Nahá¸ah al-â€˜UlamÄâ€™ fÄ« IthbÄt AwÄâ€™il al-ShuhÅ«r al-Qamariyyah bi IndunÄ«siyÄ - Hefni, Wildani (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2018)
As a largest muslim organization in Indonesia, NU has been admitted as an innovative pioneer of both hisÄb and ruâ€™yat studies which has also been academically necessary in the history of hisab and rukyat studies in Indonesia. According to NUâ€™s perspective, the year of 1984 was officially pointed to become the beginning of hisÄb and ruâ€™yat movement which is symbolized by the establishment of Lajnah Falakiyah (the agency of Islamic astronomy study) of Nahdlatul Ulama. This research aims at knowing the extent of the dynamical discourse of NU in the development of hisÄb and ruâ€™yat inquiry in Indonesia which its result has shown that within 1984-2000 there was a strained relation between NU and Indonesian government in understanding the concept of Islamic lunar month as it can be seen in a lot of differences in the determination of the initial and final month of qamariah. Meanwhile, in the aftermath of 2000s, the relation between both has dynamically walked in the effort of unification in determining the beginning and end of qamariah month.